Pedicularis cheilanthifolia var. albida (Orobanchaceae): A new record for the flora of Uttarakhand, India - Sunit Singh; Sajan Thakur; J. P. Mehta; Harish Chander (Sigmul bunryu hag-hoeji = Korean journal of plant taxonomy, 2023)
The herb Pedicularis cheilanthifolia var. albida (Pennell) P. C. Tsoong is reported and collected for the first time from the Rudraprayag District of Uttarakhand. The species was seen growing along a glacial stream in an alpine region between 4,100 and 4,400 m asl. Morphological characteristics of the species were examined and processed for herbarium deposition. To simplify taxon identification, a brief taxonomic description and illustration of the taxon are provided.